Effectiveness of insecticides for the control of Plutella xylostella (L.) (Lepidoptera: Plutellidae) and mortality of the parasitoid Diadegma insulare (Cresson) (Hymenoptera: Ichneumonidae) on brassicaceous plants - Zavala-García, Mario; Bujanos-Muñiz, Rafael; Núñez-Colín, Carlos Albrerto; Raya-Pérez, Juan Carlos; Aguirre-Mancilla, César L.; Covarrubias-Prieto, Jorge (Revista Colombiana de Entomología, 2024)
Crop production of brassicaceous crops in Mexico are affected by the attack of the diamondback moth, Plutella xylostella L. (Lepidoptera: Plutellidae). An inadequate application of insecticides indirectly affects the main parasitoid of this pest, the wasp Diadegma insulare (Cresson) (Hymenoptera: Ichneumonidae). Eight insecticide treatments and one control were evaluated using a completely randomized design with four replications. The objective of this research was to evaluate, under laboratory conditions, three organic insecticides, five synthetic insecticides and a control, to determine their effectiveness in controlling P. xylostella and its effect on the mortality of the parasitoid D. insulare. Broccoli leaf immersion method in solution with insecticides was used. Pyridalil caused the highest mortality (100 %) in the third-instar larval stage of P. xylostella at 48 h after application and mild to moderate mortality (categories 1 and 2 of the IOBC) to D. insulare at 72 hours; Naled obtained 100 % mortality in the larva and adult of P. xylostella, but also caused 100 % mortality in the parasitoid 24 h after treatment. Among the organic insecticides, Pyrethrin produced the highest mortality in P. xylostella larvae (60 %) at 72 h in the two doses used and caused a mortality of 10 % in D. insulare. Pyridalil and Emamectin Benzoate insecticides showed high effectiveness for the control of the insect-pest and had low impact on the parasitoid.